Teaching Writing Through Canva Application at MTS Al-Islamiyah Ciledug - Qondila Paulia (Penerbit STKIP PGRI Bangkalan, 2021)
This study aims to determine how effective the use of Canva application media is in teaching writing. This research was conducted in July-August at Mts Al-Islamiyah, Ciledug. Researchers used quantitative methods with pre-experimental methods by applying pre-test and post-test as instruments in collecting data. Researchers used one class in class IX-1 MTs Al-Islamiyah Ciledug as the population. The method in this study using the rendom sampling technique used in class IX-1. The mean score on the post test was 70.83 and the pre-test was 64.73. It also shows that the Tcal value (9,585) is higher than the Ttable (2.021), at the 5% significance level. If the result t-test is higher than t-table, the alternative hypothesis (Ha) is accepted, and (H0) is rejected. Based on the results of the t-test calculation above, because the positive hypothesis (Ha) is accepted, it can be concluded that the Canva Application is an effective use of media in teaching writing skills.